Spatial Audio in Virtual Reality: A systematic review - De Almeida, Gustavo Corrêa; de Souza, Vinicius Costa; Da Silveira Júnior, Luiz Gonzaga; Veronez, Maurício Roberto (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2023)
Spatial Audio represents sound across a full sphere around the listener’s position and is being widely implemented in Virtual Reality and games. However there’s not an extensive body of work in the full benefits of immersive audio in virtual reality, as well as it’s applications through these systems in the literature. This work aims, through a systematic review on the theme, to point how and where can spatial audio be of immense value to virtual reality applications, opening up a world to develop future works in mixing spatial audio content for virtual reality.